Does the impact of social transfers really matter? - Stokic, Ljiljana Pejin (Ревија за социјална политика/Journal of Social Policy, 2013)
In the last ten years Serbian government amended its two main laws related to social transfers twice, in 2004 and 2011. In both cases changes raised the value of social transfers and introduced coverage of additional vulnerable groups. Two main social transfers in Serbia are: Family financial support and Child benefits, the role of the first one is to support families whose income is bellow a minimal survival level, the role of the latter one has changed, from being an instrument for demographic boost to one which has exclusively a social role as a financial support for the low income families with children. The paper explores the real impact of these changes on the targeted population and examines if the proclaimed goals have been achieved. The underlying question is how decision makers view these two social transfers, do they consider them as a valuable instrument to enhance social inclusion of the vulnerable population or they have more bureaucratic approach, where these transfers represent only an inherited normative measure by which government claims its concern about the vulnerable population. This issue is closely related to the question of the perception of the social inclusion policy and its place in the contemporary social policy in Serbia. The paper presents findings from the available analyses on the impacts of introduced normative amendments, gives a review of the current social policy and draws attention to the lack of interest of the state’s officials on monitoring and evaluation of impacts of new legislative.
Keywords: Poverty; eligibility; living standard; financial transfers